Network model and methods for solving the k travelling salesman problem for optimisation of delivery routes - Dutin, Sergey R. (Journal of the Belarusian State University. Economics, 2023)
The article formulates a network model of the k travelling salesman problem for optimisation of delivery routes in electronic commerce. Approximate and exact methods of searching for optimal or quasi-optimal routes are proposed for the constructed model. The task of routing delivery is of great practical importance due to the rapid growth of e-commerce and it has not been sufficiently investigated due to the novelty.